Comparing Fracture Resistance of Endodontically Treated Teeth Using Different Preparation-Obturation Combinations - Zahra Sadat Madani; Akam Saeidi; Ali Bijani; Hanif Allahbakhshi; Azadeh Hesarkhani (Journal of Kerman University of Medical Sciences, 2019)
Background:One of the main reasons for extraction of endodontically treated teeth is vertical root fracture (VRF). Some factors such as root canal treatment are involved in vertical root fracture because of their potential to weaken the tooth structure. Therefore, this study aimed to investigate the effect of combining different obturation materials and rotary systems on the fracture resistance of treated teeth. Methods:Eighty extracted maxillary central incisors were selected. The coronal portions of all teeth wereremoved at the cemento-enamel junction leaving the root segment of nearly 13 mm length. Roots were randomly divided into2 groups according to the system used in root canal preparations, Group I: ProTaper, Group II: Wave 1. Each main group was further subdivided into 2 equal subgroups according to the obturation system being used, Subgroup A: ProTaper, AH26 obturator, Subgroup B: ProTaper, Bioceramic, Subgroup C: Wave 1, AH26 obturator and Subgroup D: Wave 1, Bioceramic. Fracture resistance of each sample was measured by loading in universal testing machine. The results were analyzed with two-way ANOVA followed by multiple comparison Tukey HSD test. Results: The highest mean fracture resistance value (256.7N) was associated with Soft-Core/AH26 obturation and wave one (subgroup C), while the lowest value (239.8 N) was for Bioceramic sealer and Wave 1 (subgroup D); however, there was no statistical significant difference (P>0.05) among all tested subgroups. Conclusion: All instrumentation techniques caused weakening of the root structure and made them susceptible to fracture without any significant difference and therefore alternative strategies should be considered to reinforce endodontically treated roots.